Qubbet el-Hawa, the Rock Tomb of Ishemai - Chioffi, Marco.
Tomb no. 98 of Ishemai, the sealer of the king of Lower Egypt, and other usufructuaries located in Qubbet el-Hawa and brought to light by Holled Smith at the end of the nineteenth century, was mentioned in excavation reports by Wilbour, Budge, and Bouriant. Edel, on the contrary, provided a complete analysis, published in 2008, of the tomb. Our work involved the analyzing and proposing a new transliteration and translation of the written texts in Tomb 98 and to explain why they differ from those of Edel. Here follows a transliteration and translation that is faithful to the hieroglyphs in their original state, and respects the dividing lines of the registers.The hieroglyphic text of the third register in the smaller square on the south wall is open to several alternative transliterations and translations, as noted in the comments. With their research, the authors do not intend to challenge Edel’s valuable work so much as enrich it and pay due respect for the eminent Egyptologist. This respect extends to the ancient owner and the eminent Egyptologists who first shed light on these sacred, eternal houses.